"I like them, but won't 'like' them": An examination of impression management associated with visible political party affiliation on Facebook. (August 2016) - Marder, Ben; Slade, Emma; Houghton, David; Archer-Brown, Chris
Abstract: Unlike traditional media, our interactions with political parties via social media are generally public, subject to scrutiny by others and, consequently, a self-presentation concern. This paper contributes to theory on impression management within social network sites (SNSs) by providing an understanding of the effect of visible affiliation on page 'Liking' behavior in the context of political parties; specifically, the possible association with social anxiety and the use of protective impression management. We predict that while users may be motivated to 'Like' a political party, some may feel socially anxious about the impressions their friends may derive from this action, and so ultimately choose to refrain from 'Liking' the party. Furthermore, we propose a new function of 'Secret Likes' (i.e. 'Likes' that others cannot see) as a means to increase gateway interactions. A survey of eligible voters ( n = 225) was conducted in the month prior to the 2015 UK general election, examining behavior associated with the Facebook pages of the two largest political parties. Results support that conspicuous affiliation with political parties indeed hinders intention to 'Like' political pages and is associated with social anxiety. 'Secret Likes' were found to be a successful method to increase gateway interactions. In addition to the theoretical contribution, implications for political party communications and site designers are considered. Highlights: Examines self-presentational concern on 'Liking' political parties on Facebook. Intention to 'Like' is lower if it is perceived to create negative impressions. Social anxiety is an important determinant of intention to 'Like'. People show higher intention to 'Like' when secret vs. visible to others.